Retroperitoneal Abscess in Pediatrics: Case Report - Flores-Uzcanga, Maura Alicia; Torres-Mata, Elvia; Flores-López, Alejandro Alberto (British Journal of Healthcare and Medical Research, 2024)
Retroperitoneal abscesses are unusual phenomena with hidden and insidious presentations. Often, there is a lack of abdominal signs, leading to delays in drainage and high mortality rates. We present a case of retroperitoneal abscess in a 13-year-old male patient with no significant medical history. Clinically, he presented a two-week course of fever, headache, vomiting, anorexia, and abdominal pain. Abdominal ultrasound revealed a right subdiaphragmatic collection. Likewise, CT scan showed a perihepatic collection with the presence of gas. The patient was successfully treated with broad-spectrum antibiotics and percutaneous drainage.